A review of non-native seaweeds from California, USA and Baja California, Mexico - Ann Miller, Kathy; Aguilar-Rosas, Luis Ernesto; Pedroche, Francisco F. (HIDROBIOLÓGICA, 2017)
The seaweed flora of California, USA and Baja California, Mexico is a world-class treasure. The magnificent diversity and abundance of seaweed populations reflect the dramatic sweep of these rich coastal environments and habitats, from the Pacific Northwest to the subtropics, including rocky shores and reefs, sandy beaches, and offshore islands. Novel species have joined the flora, mostly via unintentional introductions of non-indigenous species by humans. Most of the 29 non-native seaweed species recorded from this coast originated in Asia. Many have been discovered within the last 30 years. Although the vectors that bring these plants or their propagules to the California and Baja California coasts (international shipping and shellfish aquaculture) may or may not be increasing within that time span, the conditions for the establishment of non-native species seem to have improved. Climate change, including the frequency and severity of ENSO events, may be responsible for creating space, diminishing competition, and permitting the persistence and spread of non-native species. Here we review these non-native seaweed species and speculate on the link between their establishment and climate change.